Combined Control Scheme for Monitoring Quality Characteristics (Global Journal of Science Frontier Research, 2014)
In the literature, the Exponentially Weighted Moving Average (EWMA) and Exponentially Weighted Moving Variance (EMWV) control schemes have been used separately to monitor the process average and process variability respectively. Here the two are combined and applied on simulated process with different level of variation. The control limit interval (CLI) and the average run length (ARL) were evaluated for the combined chart. The combined chart performed better than the two independently. Furthermore, an algorithm was developed for the two control charts and implemented on visual basic VB6.0. The obtained results show that the combined EWMA and EWMV control chart is very sensitive in detecting shift in production process and every shift in the process mean is always preceded by shift in the process variability.
Keywords: statistical process control; control chart; exponentially weighted moving average (ewma); exponentially weighted moving variance (emwv)